2021
DOI: 10.1021/acsomega.0c05565
|View full text |Cite
|
Sign up to set email alerts
|

Sanjie Yiliu Formula Inhibits Colorectal Cancer Growth by Suppression of Proliferation and Induction of Apoptosis

Abstract: Colorectal cancer (CRC) is one of the most common malignancies worldwide. As current therapies toward CRC, including chemotherapy and radiotherapy, pose limitations, such as multidrug resistance (MDR) as well as the intrinsic and potential cytotoxic effects, necessitating to find more effective treatment options with fewer side effects, traditional Chinese medicine (TCM) has an advantage in complementary therapies. In the present study, 3-(4,5-dimethylthiozol-2-yl)-2,5-diphenyltetrazolium bromide (MTT assays),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In the treatment of PLGC, TCM acts mainly by regulating cell proliferation and apoptosis ( Xu et al, 2022 ). The role of TCM in the treatment of CRC has been reported, and data support the benefits of TCM herbals as a long-term therapeutic strategy for patients with stage II and III CRC ( Li-Weber, 2013 ; Li et al, 2021b ; Tang et al, 2021 ). TCM can interact with gut microbiota, which has a considerable influence on the therapeutic effects ( Feng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 83%
“…In the treatment of PLGC, TCM acts mainly by regulating cell proliferation and apoptosis ( Xu et al, 2022 ). The role of TCM in the treatment of CRC has been reported, and data support the benefits of TCM herbals as a long-term therapeutic strategy for patients with stage II and III CRC ( Li-Weber, 2013 ; Li et al, 2021b ; Tang et al, 2021 ). TCM can interact with gut microbiota, which has a considerable influence on the therapeutic effects ( Feng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 83%
“…. Multiple synthetic drugs exhibit substantial protection against oxidative stress/damage, but they have many adverse effects like cardiovascular diseases, hepatotoxicity, nephrotoxicity, and gastrointestinal tract problems. , Alternative options for safer use are the consumption of traditional medicine, natural antioxidants from food supplements, and herbal and polyherbal formulations . Doxorubicin has been used extensively and effectively as a broad-spectrum anticancer drug, although its medical use has been limited due to its severe dose-dependent cardiotoxicity in humans .…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 Alternative options for safer use are the consumption of traditional medicine, natural antioxidants from food supplements, and herbal and polyherbal formulations. 17 Doxorubicin has been used extensively and effectively as a broad-spectrum anticancer drug, although its medical use has been limited due to its severe dose-dependent cardiotoxicity in humans. 18 Experimental and clinical analysis suggested that increased oxidative stress and/or ROS play a crucial role in consequent cardiomyopathy and cardiac failure related to the doxorubicin treatment model.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment selected four CRC cells and found that the Sanjie Yiliu formula (SJYLF) significantly inhibited the activity of HCT-8, SW480, HT29, and DLD-1 CRC cells. SJYLF components, consisting of Fabanxia, Glabrous Sarcandra herb, Thunberg Fritillary bulb, and ground beetle species, initiated apoptosis through downregulating Bcl-2, cylin D1, and CDK4 protein, as well as increasing Bax expression ( Tang et al, 2021 ). Besides, Sijunzi decoction (SJZD) consistsing of Panax ginseng C.A.Mey., Atractylodes macrocephala Koidz., Poria cocos Wolf., and Glycyrrhiza uralensis Fisch., proportioned at a ratio of 2:2:2:1 and clinically used in treating CRC.…”
Section: Application Of Prescriptions In Crcmentioning
confidence: 99%